Pesticides in a warmer world: Effects of glyphosate and warming across insect life stages. (15th August 2022) - Stahlschmidt, Z.R.; Whitlock, J.; Vo, C.; Evalen, P.; D, Bui
Abstract: Glyphosate (GLY) is a broad-spectrum herbicide that is the most commonly applied pesticide in terrestrial ecosystems in the U.S. and, potentially, worldwide. However, the combined effects of warming associated with climate change and exposure to GLY and GLY-based formulations (GBFs) on terrestrial animals are poorly understood. Animals progress through several life stages (e.g., embryonic, larval, and juvenile stages) that may exhibit different sensitivities to stressors. Therefore, we factorially manipulated temperature and GLY/GBF exposure in the variable field cricket ( Gryllus lineaticeps ) during two life stages—nymphal development and adulthood—and examined key animal traits, such as developmental rate, body size, food consumption, reproductive investment, and lifespan. A thermal environment simulating future climate warming obligated several costs to fitness-related traits. For example, warming experienced during nymphal development reduced survival, adult body mass and size, and investment into flight capacity and reproduction. Warming experienced by adults reduced lifespan and growth rate. Alternatively, the effects of GBF exposure were more subtle, often context-dependent (e.g., effects were only detected in one sex or temperature regime), and were stronger during adult exposure relative to exposure during development. There was evidence of additive costs of warming and GBF exposure to rates of feeding and growth in adults. Yet, the negative effect of GBF exposure to adult lifespan did not occur in warming conditions, suggesting that ongoing climate change may obscure some of the costs of GBFs to non-target organisms. The effects of GLY alone (i.e., in the absence of proprietary surfactants found in commercial formulations) were non-existent. Animals will be increasingly exposed to warming and GBFs, and our results indicate that GBF exposure and warming can entail additive costs for an animal taxon (insects) that plays critical roles in terrestrial ecosystems. Graphical abstract: Image 1 Highlights: Animals' responses to warming and glyphosate-based herbicides are poorly understood. Here, warming affected fitness-related traits in crickets more than herbicide exposure. Costs of herbicide exposure to lifespan were obscured by warming. Exposure to glyphosate alone did not influence any measured trait.